Tożsamość społeczno-przestrzenna miasta satelitarnego. Przykład Lubonia koło Poznania - Nowak, Marek; Bernaciak, Anna (Człowiek i Społeczeństwo, 2023)
Article analyses the case study of Luboń, a town of 30,000 people neighbouring Poznań. It addresses the issue of socio-spatial identity. The concept of the socio-spatial identity of a city is analysed on the basis of traditional conceptualisations but also with reference to a system theory, which makes it possible to look at the functioning of a city from its own perspective (the notion of „autopoiesis”). In addition to an understanding of the system, this curates a historical perspective in the analysis of contemporary urban functioning. The authors of the text ask three research questions: about the sense of connection to the city, about the place of the space of Luboń in the everyday practices of its inhabitants, and the ideas of the city’s inhabitants about themselves (self-image of a Luboń resident). The conclusions from the analysis of the empirical material are aimed at describing the barriers to the articulation of the identity of the city’s inhabitants inherent in the developmental characteristics of satellite towns in a specific social and institutional context. The study is based on a 3-year research project carried out at the Faculty of Sociology of Adam Mickiewicz University with the participation of students, as part of a student internship, in cooperation with a researcher from Poznań University of Economics and Business. The project involved two questionnaire surveys and qualitative research based on secondary data analyses, expert interviews and focus group interviews, and research walks between 2021 and 2022.